Cover Feature: Development of an Engineered Photoactive Yellow Protein as a Cross‐Linking Junction for Construction of Photoresponsive Protein‐Polymer Conjugates (ChemPhotoChem 6/2019). Issue 6 (5th June 2019) - Ui, Mihoko; Miyauchi, Yusuke; Inoue, Masataka; Murakami, Makoto; Araki, Yasuyuki; Wada, Takehiko; Kinbara, Kazushi
Abstract : The Cover Feature illustrates a protein–polymer conjugate consisting of a methacrylate‐type synthetic polymer covalently crosslinked by genetically engineered photoactive yellow protein bearing 5 homopropargylglycine residues (Hpg5‐PYP). The protein–polymer conjugate showed a photoresponsive viscosity change upon irradiation with blue light at 25 °C. More information can be found in the Communication by M. Ui et al. on page 356 in Issue 6, 2019 (DOI: 10.1002/cptc.201900024 ).